PRODUCTIVITY OF RESOURCE-SAVING AGRO TECHNOLOGIES OF GROWING MEDICINAL DATURA INNOXIA MILL - Pulatov, S.M.; Muminov, K.M. (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the culture of cultivation of Datura Innoxia Mill in typical sandy soils of Tashkent region is 70x70, with the temperature of 15-17 0С in the second or third April of a depth of 3-4 sm. Phase -20-1 planting, using nitrogen fertilizers (N120 kg/ha) in the form of P-90, K-90 kg/ha in the form of ammonium sulfate [(NH4)2SO4], creating favorable conditions for plant growth and development. environmentally friendly 11,6-12,0 centners/ha There are data on resource-saving agricultural technology of dry leaves with high narcotic value and 17,4-18,5 kg/ha.